A debreceni Kossuth Lajos Tudományegyetem archontológiája 1950–1990 XI. rész - Mudrák, József (Gerundium, 2019)
The Archontology of Lajos Kossuth University of Arts and Sciences (1950–1990), Part XI: University Library. The Archontology of Kossuth University for the School of Arts, the School of Sciences, and for the so-called „Central Units” between January 1, 1950, and December 31, 1990, was compiled on the basis of the personal cards and personal files of the Personnel Department of the Rector’s Office, and the scantily documented section for the 1950s was supplemented from the annually arranged documentary material of the Personnel Office. Even so, however, the existing material fails to be complete. It is impossible to compile the archontology with perfect accuracy. Part XI presents the complete list pertaining to the University Library from director-general to janitor.